WOMEN'S PERCEPTIONS OF SPIRITUALITY AND MATERNAL EMPOWERMENT DURING HYDROTHERAPY IN THE FIRST STAGE OF LABOR: A PHENOMENOLOGICAL STUDY - Nova Avianti Rahayu; Utami Lisma Septadara (Jurnal Kebidanan Khatulistiwa, 2026)
Background: Childbirth is a multidimensional experience involving physical, psychological, emotional, and spiritual aspects of women. Hydrotherapy as a non-pharmacological method is known to improve relaxation and comfort during labor, yet women’s experiences of spirituality and empowerment during hydrotherapy remain underexplored. Objective: This study aimed to explore women’s perceptions of spirituality and empowerment during hydrotherapy in the first stage of labor. Methods: This study used a qualitative approach with a descriptive phenomenological design. The research was conducted in August 2025 until January 2026 in Pekanbaru. Participants consisted of six women who had experienced hydrotherapy during the first stage of labor and were selected using purposive sampling. Data were collected through semi-structured in-depth interviews and analyzed using Braun and Clarke thematic with six-step analysis. Results: Five major themes emerged from the study, namely spiritual closeness, inner strength and self-confidence, self-control during labor, gratitude and positive childbirth experiences, and maternal empowerment. Hydrotherapy helped mothers feel calmer, closer to God, more confident in facing labor, better able to regulate breathing and emotions, and more empowered during childbirth. Conclusion: Hydrotherapy during the first stage of labor not only provides physical benefits in reducing labor discomfort but also positively affects spirituality, psychological well-being, and maternal empowerment.